Restoring Authenticity: Literary, Linguistic, and Computational Study of the Manuscripts of Tchaikovsky’s Children’s Album - Evgeny Pyshkin; John Blake (Arts)
This research contributes to the studies on the origins and transformations of Tchaikovsky’s Children’s Album, Op. 39 using the linguistic methods of discourse, metaphor, and comparative analysis to explore a number of connected questions and their impact on how the audiences and scholars perceive and understand the compositions. These methods are supported by the technology provided by computational linguistics, such as large language models along with music analysis algorithms based on signature pattern elicitation. This article examines how artificial intelligence technologies can shed light on the differing views on the Children’s Album. The meanings and implications of the published reordering of the pieces are explored. The influence of Schumann’s Album for the Young and the broader pedagogical and cultural significance of editorial transformations is investigated. Through this interdisciplinary approach, this study offers new insights into the compositional intent and interpretive possibilities of Tchaikovsky’s work. The presented results of the musicology, literary, computational, and linguistic analyses complement the few scholarly studies aimed at unveiling the intriguing metaphors and connections of the Children’s Album, which tend to remain in the shadows of his larger-scale piano and symphonic works.